Change in Shear Elastic Modulus of Thigh Muscle by Changing Muscle Length Using Ultrasound Shear Wave Elastography in Beagle Dogs - Shimizu, Miki; Ito, Yu (Veterinary and Comparative Orthopaedics and Traumatology, 2019)
Objectives This study investigated the relationship between the change in the shear elastic modulus and the change in muscle length using ultrasound shear wave elastography.Study Design Four thigh muscles, cranial part of the sartorius, vastus lateralis, biceps femoris and semitendinosus muscles, of 21 pelvic limbs in 12 clinically healthy Beagle dogs were used. The muscle length was estimated using a radiograph and the flexed and extended positions of the coxofemoral and stifle joints, respectively. The shear elastic modulus (kPa) was measured in two joint positions using ultrasound shear wave elastography. Shear elastic modulus was expressed as median of 10 consecutive measurements. The percentage change of elastic modulus was calculated from the shear elastic modulus in elongated condition and pre-elongated condition of muscle.Results The elastic modulus of all muscles increased when the muscle was elongated. The shear elastic modulus for both joint positions and the percentage change of the shear elastic modulus (%) in cranial part of the sartorius were highest in all muscles. Intra-observer correlation coefficient (1.2) was 0.75 to 0.96 and intra-observer correlation coefficients (2.2) was 0.46 to 0.96.Conclusion This study revealed that the shear elastic modulus of muscle was changed by the change in muscle length and increased when the muscle was elongated. Ultrasound shear wave elastography can be used to assess the elastic properties of canine muscle.
Keywords: joint angle; muscle stiffness; passive tension; ultrasound; shear wave elastography